Implementasi Model Pembelajaran Direct Instruction Menggunakan Pendekatan Saintifik pada Mata Pelajaran Ekonomi Kelas X MAN 2 Malang - Santya Ulfah; Anjar Mega Utami; Septiani Satriani Purnama Putri; Imam Muklis; Rusman Hadi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
The Economics learning at MAN 2 Malang uses a direct instruction model with alearning approach scientific. The purpose of this study was to determine whether the direct instruction learning model was appropriate for teachers to use in the online learning process on student learning outcomes. This study used a quasi-experimental method with one group design pretest and posttest. The sampling process uses saturated samples by means of non-probability sampling. This research was conducted in five meetings. The research subjects were students of class X IPS 3 MAN 2 Malang, totaling 22 people. From the results of the study obtained an average post-test result of 60.54> from the results of the pre-test an average of 50.45. There is an increase from the results of the pre-test to the results of the post-test. However, the comparison of pre-test and post-test scores has not yet reached the KKM. So, from the results of the research and analysis of the t test, it shows that the economic learning outcomes of students in class X IPS 3 Man 2 Malang after applying the direct instruction model are significantly incomplete. This is shown from the final test results obtained t count = 1.98 with degrees of freedom dk = n – 1 = 22 – 1 = 20, = 0.05 obtained t table = 1.72 so that t count < t table is 1, 98 < 2.08 then H0 is rejected, and Ha is accepted. DOI: https://dx.doi.org/10.17977/UM014v14i22021p160